2016
DOI: 10.1111/imj.13025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adult patients with chronic liver failure for liver transplantation in 2015: who and when?

Abstract: In 2015, there are a few absolute contraindications to liver transplantation. In adult patients, survival post-liver transplant is excellent, with 1-year survival rate >90% and 5-year survival rates >80% and predicted median allograft survival beyond 20 years. Patients with a Child-Turcotte Pugh score ≥9 or a model for end-stage liver disease (MELD) score >15 should be referred for liver transplantation, with patients who have a MELD score >17 showing a 1-year survival benefit with liver transplantation. A car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…It has been shown that the MELD score can serve as an indicator of multi-organ failure [ 5 ]. The score is currently used in the allocation of organs for patients waiting for liver transplantation as it also correlates significantly with waiting list mortality [ 6 ]. The MELD score captures derangements in two critical organ systems: kidney and liver.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the MELD score can serve as an indicator of multi-organ failure [ 5 ]. The score is currently used in the allocation of organs for patients waiting for liver transplantation as it also correlates significantly with waiting list mortality [ 6 ]. The MELD score captures derangements in two critical organ systems: kidney and liver.…”
Section: Introductionmentioning
confidence: 99%
“…It was believed two to three decades ago that systemic vasodilation that occurs in ESLD is able to protect the cardiovascular system from coronary artery disease (CAD). 35 However, current evidence suggests that CAD is highly prevalent in LT candidates. The overall prevalence of CAD in chronic liver disease has been reported to be between 2%-28%, increasing the mortality and morbidity rates after liver transplantation.…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…It was believed two to three decades ago that systemic vasodilation that occurs in ESLD is able to protect the cardiovascular system from coronary artery disease (CAD) 35 . However, current evidence suggests that CAD is highly prevalent in LT candidates.…”
Section: Etiologymentioning
confidence: 99%
“…A presença do apoio e suporte social foi elencada nos artigos como um critério a ser avaliado e considerado na seleção para a listagem do transplante hepático. Como justificativa principal para isso, os estudos demarcam que a abstinência convencionada para a realização do procedimento (consenso encontrado nos estudos, de um mínimo de seis meses abstinentes para ser elegível ao recebimento do órgão) está diretamente relacionada à presença ou ausência de pessoas que auxiliem o indivíduo a manter-se sem o uso de álcool (Dom, Francque & Michielsen, 2009;Heyes et al, 2016;McCaughan et al, 2016;Satapathy et al, 2015;Telles-Correia, 2011).…”
Section: Funções Da Rede Socialunclassified